O desenvolvimento do pensamento verbal, da atenção voluntária e a linguagem interna como autorreguladora da aprendizagem de jovens e adultos do ensino médio em prisões - Donegá, Magda Sílvia (2021)
The Cultural-Historical Theory was the basis of this research, which had as its starting point the following question: What kind of intentional mediators would be necessary according to the Cultural-Historical Theory for the development of voluntary attention of high school students in prisons? The objectives were: to analyze the concept of learning in the Cultural-Historical Theory, through the deepening of the concepts of voluntary attention, verbal thought, zone of proximal development; identify and analyze the kind of mediators that are necessary for school learning by young people and adults; relate the concepts of study activity and voluntary attention to the kinds of mediators that are necessary for school learning by young people and adults in the context of deprivation of freedom. The methodology was based on theoretical research, subsidized by Vigotsky's genetic method and also by Salvador's informative readings. The proceedings involved the study of the primary sources of Cultural-Historical Theory, mainly present in the works of Vigotsky, Leontiev, Luria, Bozhovich, Schúkina, Petrovski, Elkonin and Davidov. Data collection was carried out in electronic bibliographic databases, media, books and official documents. For the analysis of the data we formulated four theoretical guidelines for analysis: 1) the dynamic development of character and its relation with the practice of crimes, the meaning and social purpose of prison, and some considerations about redemption; 2) analysis of the application of the Cultural-Historical Theory in the educational practice in Brazil: principles for teaching practice and the cognitive interest focused on the subjects as a way to develop the student's voluntary attention; 3) adulthood based on Cultural-Historical Theory, the development of verbal thought in adults with low schooling and the externalization of internal language as a mechanism for learning in adulthood; 4) teaching practice and the development of students’ voluntary attention in Young people and Adults Education at the high school in a context of deprivation of liberty. The results indicated the importance of the evolution of the level of generalization from the everyday concept to the level of scientific concepts in prisons and, therefore, that the teacher is the main mediator of learning, and beyond the specific formation in the discipline, he or she needs to have specific formation in the context of deprivation of freedom when teaching for adults. It happens because there are several specificities for the development of educational practice in prisons, among which we highlight: the psychological tensions experienced by the students, the student's transit situation at the time of serving a sentence, the human relationship needs. Therefore, the teacher needs to consider this context of deprivation of freedom to teach without losing the focus on teaching scientific concepts while guiding human relationships during the learning process based on the collaborative principle. Another important result is related to the need of the development of voluntary attention in students, which also enables the development of cognitive interest for the necessary study activity. In this process, the enhancement of the internal language works as a self-regulating mechanism of voluntary attention and adult student learning.